Influence of the polymer matrix on the viscoelastic behaviour of vitrimers. Issue 33 (15th May 2020) - Spiesschaert, Yann; Taplan, Christian; Stricker, Lucas; Guerre, Marc; Winne, Johan M.; Du Prez, Filip E.
Abstract : Vitrimers, an emerging field of research, in which still many fundamental aspects of material design remain to be explored. Here, we systematically explore the effect of the choice of the matrix on a dynamic exchange reaction in a polymer network. Abstract : Vitrimer materials are a rapidly growing field of research, in which still many fundamental aspects of material design remain to be explored. In this study, we report a systematic study about the effect of the choice of the matrix on a dynamic covalent bond exchange reaction in a polymer network. In some way, this investigation follows the logic of a 'solvent effect' study that is typical for the development of an organic reaction or synthetic method in solution. Thus, this work constitutes a study of matrix effects on the viscoelastic properties of vitrimers, in particular with regard to their stress-relaxation behaviour. For that purpose, the dynamic transamination within vinylogous urethanes (VU) vitrimers, derived from a wide range of different commercially available diols, was chosen as vitrimer chemistry reaction platform. Additionally, the influence of the molecular weight, and thus the cross-link density, was also investigated using two oligomeric diols of different molecular weights. It was found that changing the molecular weight resulted in vitrimers with significantly different activation energies (from 68 to 149 kJ mol −1 ) and relaxation times (from 7 to 230 min at 140 °C). These remarkable results suggest that both the molecular weight and the nature of the polymer matrix have a large influence on the resulting viscoelastic properties. However, no straightforward prediction of relaxation times or activation energies is possible at this stage, and it becomes clear that many more structure–reactivity studies will be required to arrive at a more general understanding of the factors that underly vitrimer properties.